2019
DOI: 10.4103/sajc.sajc_427_18
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticide exposure as a risk factor for breast cancer in young Indian women: A case–control study

Abstract: Background:Incidence rates of breast cancer are showing an increasing trend in young women (≤40 years) in India. Risk for breast cancer in this age group can be attributed only partially to various known risk factors. Environmental exposure to organochlorine (OC) compounds has been identified as a potential risk factor. However, the possible role of OC compounds in increasing breast cancer risk in young women has not been explored. This case–control study was planned with the objectives to assess the serum lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…This study revealed that the most frequent stage of breast cancer detected was Stage II (36%), and invasive ductal carcinoma was the most common type (78.6%) in those patients ( 52 ). Additionally, it was found that DDE levels were higher in patients with breast cancer compared with in healthy individuals ( 52 ).…”
Section: Effects Of Edcs On Mammary Gland Tissuementioning
confidence: 81%
See 2 more Smart Citations
“…This study revealed that the most frequent stage of breast cancer detected was Stage II (36%), and invasive ductal carcinoma was the most common type (78.6%) in those patients ( 52 ). Additionally, it was found that DDE levels were higher in patients with breast cancer compared with in healthy individuals ( 52 ).…”
Section: Effects Of Edcs On Mammary Gland Tissuementioning
confidence: 81%
“…A case-control study in patients with breast cancer in India during 2015–2016 analyzed the serum levels of organochlorine compounds, such as hexachlorocyclohexane (HCH)-α, β, γ, endosulfan, DDT and its metabolites, among other compounds ( 52 ). This study revealed that the most frequent stage of breast cancer detected was Stage II (36%), and invasive ductal carcinoma was the most common type (78.6%) in those patients ( 52 ). Additionally, it was found that DDE levels were higher in patients with breast cancer compared with in healthy individuals ( 52 ).…”
Section: Effects Of Edcs On Mammary Gland Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Kaur N, et al [20] report significantly higher blood levels of α-, β-, γ-HCH, heptachlor, DDE, endosulfan 1 & 2, and dieldrin isomer levels among breast cancer patients when compared with controls. Young women with breast cancer were found to have significantly higher serum levels of all the OC compounds except aldrin, p,p'DDT and methoxychlor.…”
Section: Resultsmentioning
confidence: 99%
“…There has been recent concern over the use of pesticides, including OPs, and their implications on public health [ 52 , 53 , 54 , 55 , 56 , 57 ]. For example, several types of insecticides, fungicides, and herbicides have been found to be positively associated with breast cancer risk [ 58 , 59 , 60 , 61 ]. While the IARC classified malathion as “probably carcinogenic to humans” [ 18 ] and a recent meta-analysis indicated a statistically significant association between OP exposure and non-Hodgkin’s lymphoma (NHL) risk [ 17 ], a comprehensive review of studies examining the relationships between OPs and breast cancer risk had not been done.…”
Section: Discussionmentioning
confidence: 99%